Low-Fat and High-Quality Fermented Sausages - Tremonte, Patrizio (Microorganisms, 2020)
The present study, considering for the first time microbiological concerns due to the use of lemon albedo as a fat replacer, aimed at the selection of an anti-Listeria strain to be used as protective culture in low-fat southern Italian fermented sausages. In fact, these kinds of products require appropriate bio-protective strategies to avoid risks due to Listeria monocytogenes. Sixty-seven Lactiplantibacillus plantarum strains isolated from diverse sources were screened for their antimicrobial activity and their interaction with starter strains (Latilactobacillus sakei 152 and Staphylococcus xylosus MVS9). Lactiplantibacillus plantarum Lpls100, highlighting both listericidal activity and the ability to promote Staphylococcus xylosus MVS9 growth, was used as a protective strain in low-fat fermented sausages prepared with lemon albedo as a fat replacer. The effect of the albedo and the protective strain on the fermentation process and the final quality was ascertained. Results highlighted that the use of the albedo did not affect the growth of starter strains and enhanced some quality features, such as fatty acid profiles and certain sensory attributes. However, the albedo also produced a slow decrease in water activity, compromising the microbial quality. The anti-Listeria strain, enhancing coagulase negative cocci growth and exerting antimicrobial activity, avoided the inconveniences caused by the use of the albedo. Moreover, the anti-Listeria effectiveness was assessed through a challenge test using a Listeria cocktail. The study revealed that Lactiplantibacillus plantarum Lpls100, regardless of the presence of the albedo, assures a prompt inhibition of Listeria spp. Therefore, its use could be an important contribution to the quality of low-fat fermented sausages.